ANALISIS PENGARUH NILAI KONDUKTIVITAS HIDRAULIK DAN DISPERSIVITAS DINAMIK TERHADAP REMEDIASI AIR TANAH MENGGUNAKAN SIMULASI NUMERIK - Agus Mochamad Ramdhan; Arifin Arifin; Erik Hermawan; Lambok M. Hutasoit (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2021)
Groundwater remediation is one of the solutions to restore the contaminated groundwater. This study was conducted to determine the effect of hydraulic conductivity and dynamic dispersivity on the groundwater remediation effectiveness. As a case study, in 2020, in an area located in Balikpapan, groundwater remediation will be carried out by injecting water containing NaOH through five wells and pumping it back through five wells to form a cycle. The method used is a numerical simulation consisting of groundwater flow simulation, mass transport, and sensitivity analysis. The results show that it takes 124 to 300 days for the injected NaOH to arrive at the pumping wells. The sensitivity analysis results show that when the hydraulic conductivity value is ten times greater, the time required is reduced to 84 to 172 days. Meanwhile, when the dynamic dispersivity is twice larger, the time required is reduced to 75 to 189 days. These results indicate that the groundwater remediation method will be effective for aquifers with high hydraulic conductivity and dynamic dispersivity values. For the study area, the groundwater remediation is suggested to be carried out by increasing the number of injection and pumping wells with a relatively close distance, i.e., around 10 meters, so that NaOH arrives at the pumping wells more quickly.Keywords: groundwater, remediation, hydraulic conductivity, dynamic dispersivity, numerical simulation